(untitled) (Journal of International Studies, 2020)
In November 2004 Chinese President Hu Jintaoâ€™s first tour of Latin America marked the beginning of a new phase in Beijingâ€™s relationship with the region. Since then China has followed a three-fold political and economic strategy towards Latin America: first, to secure the provision of oil, minerals and agricultural products; second, to create access to new markets for the countryâ€™s growing export volume of manufactured products; and third to make sure that Latin American governments adhere to the â€˜one China principleâ€™ in their foreign relations. This is of particular importance vis-Ã -vis Latin America where China had previously lost diplomatic ground when some states officially recognised Taiwan. The article asks as to whether and what extent China and Latin America countries have become economic and strategic partners. Do Latin American governments play the China card to hedge against Washington? Special emphasis is given to the case of Ecuador which exemplifies the PRCâ€™s growing prominence as an actor in Latin America. When Chinese foreign policy makers began to show some interest in Latin America during the early 1960s Ecuador was not a priority. However, the PRC has significantly strengthened its interests towards, and presence in, Ecuador since 2005. The provision of oil but also metals â€“ primarily copper and cold - and increasingly agricultural products has taken centre-stage in Beijingâ€™s strategy towards the Andean country. The article argues that while Chinaâ€™s influence in Latin America has undoubtedly increased significantly during the last half-decade, its role is still overshadowed by the US.